PENGARUH RETURN ON ASSETS DAN PRICE EARNING RATIO TERHADAP HARGA SAHAM PADA PT MATAHARI DEPARTEMENT STORE TBK TAHUN 2014 – 2023 - Oksami, Aru; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of Return On Assets and Price Earning Ratio on share prices at PT Matahari Department Store Tbk. The method used in this research is a descriptive quantitative method. The sampling technique used was purposive sampling in the form of the financial reports of PT Matahari Department Store Tbk for ten years for the period 2014-2023. Data analysis uses the classic assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination and hypothesis testing using the SPSS 25 approach. The results of this research are that Return On Assets does not have a significant effect on Stock Prices. hypothesis test obtained t count < t table or (0.476 < 2.306). Price Earning Ratio has a significant effect on share prices. hypothesis test obtained t count > t table or (7.024 > 2.306). The determination value was 86.5% while the remaining 13.5% was influenced by other factors that were not researched. Return On Assets and Price Earning Ratio have a significant effect on Stock Prices with the regression equation Y = 0.273 + 0.050X1 + 4.505X2. Hypothesis testing obtained calculated F value > F table or (22.396 > 4.350). Thus, there is a significant influence of Return On Assets and Price Earning Ratio on share prices.